Nickel-catalyzed synthesis of (E)-olefins from benzylic alcohol derivatives and arylacetonitriles via C–O activation. Issue 10 (24th December 2015) - Xiao, Jing; Yang, Jia; Chen, Tieqiao; Han, Li-Biao
Abstract : An efficient Ni-catalyzed synthesis of ( E )-olefins using the readily available benzylic alcohol derivatives and arylacetonitriles is described. This transformation should proceed via a tandem process involving nickel-catalyzed cross coupling via C–O activation and subsequent stereoselective E2 elimination. Abstract : An efficient Ni-catalyzed synthesis of ( E )-olefins using the readily available benzylic alcohol derivatives and arylacetonitriles is described. This transformation should proceed via a tandem process involving nickel-catalyzed cross coupling via C–O activation and subsequent stereoselective E2 elimination.